Manajemen Penerimaan Peserta Didik Baru Secara Online di SMPN 3 Kota Palangka Raya - Rudie, Rudie (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2021)
This research aims to describe the management of the acceptance of new learners online in the era of the covid 19 pandemic in SMP Negeri 3 Palangka Raya. The problem raises the management of new student admissions conducted online. To map the management problems, researchers highlight aspects of planning (planning), organizing (organizing), leadership (leading), directing , driving (actuating), and control (controling). The research method using qualitative approach, which produces description data, is carried out by means of observation, documentation and interviews with principals and teachers involved in the admission committee of new learners in Christian Junior High School and State Junior High School 3 Palangka Raya Year of study 2020/2021. Penelitian ini bertujuan untuk mendeskripsikan manajemen penerimaan peserta didik baru secara online era pandemi covid 19 di SMP Negeri 3 Palangka Raya. Permasalahan mengangkat manajemen penerimaan peserta didik baru yang dilakukan secara online. Untuk memetakan permasalahan manajemen tersebut, peneliti menyoroti aspek perencanaan (planning), pengorganisasian (organizing), pemimpinan (leading), pengarahan (directing), penggerakan (actuating), serta pengendalian (controling). Metode penelitian menggunakan pedekatan kualitatif, yang menghasilkan data deskripsi, dilakukan dengan cara observasi, dokumentasi dan wawancara terhadap Kepala Sekolah dan Guru yang terlibat dalam Panitia penerimaan peserta didik baru di SMP Kristen dan SMP Negeri 3 Palangka Raya Tahun pelajaran 2020/2021.